Therapeutic Potential of Snakehead Fish (Channa striata) Skin Collagen Hydrogel in Third Degree Burn Wound Healing: A Systematic Review - Maya Ulfah; Andriansyah; Tsabita Putri Mahyundari; Hana Azzah Sulya; Ratu Indah Mustika; Nur Indah Fitri Yani; Fadhillah Gusnita Zahra4 (Jurusan Farmasi Fakultas Kedokteran Universitas Lampung, 2026)
Third-degree burn wounds represent a severe medical challenge, often resulting in extensive tissue damage, prolonged recovery, and significant morbidity. Current therapeutic approaches frequently face limitations, including inadequate healing, infection risks, and suboptimal cosmetic outcomes. Advanced wound dressings are sought to enhance regeneration and functional recovery. This systematic review synthesises the existing literature on the therapeutic potential of snakehead fish (Channa striata) skin collagen hydrogels for third-degree burn wound healing. Methodologically, a comprehensive search was conducted across three major databases, adhering to PRISMA guidelines, to identify studies published between 2015 and 2026. The review scrutinises the characteristics of snakehead fish skin collagen, including its extraction methods and physicochemical properties, alongside the specific attributes of hydrogels, such as thermosensitivity and the integration of nanoemulsions. Furthermore, it details the complex mechanisms of burn wound healing and evaluates the documented effectiveness of fish collagen-based hydrogels in preclinical models of severe burns. A comparative analysis with conventional dressings highlights the unique advantages and existing limitations of this biomaterial. The synthesis reveals a scarcity of specific studies focusing on Channa striata skin collagen hydrogels for third-degree burns, with most research concentrating on general fish collagen or less severe burn models. Identified research gaps include the need for more targeted formulations, comprehensive preclinical evaluations in third-degree burn models, and subsequent clinical translation. This review underscores the promising biocompatibility and regenerative capacity of snakehead fish skin collagen hydrogels, positioning them as a viable direction for future wound care innovation, provided these research limitations are addressed.